Effects of Different Plant Hormones on Callus Induction and Root Formation of Eggplant (Solanum melongena L.) - AL-Saady, Hassan A.A.; El-Kaaby, Ekhlas A.J.; Al-Shimmary, Lameaa A.M.; Al-Aubiady, Ashwaq A. (Iraqi Journal of Science, 2026)
A study was undertaken in the tissue culture laboratory of the Genetic Engineering Department, Directorate of Agricultural Research, Ministry of Science and Technology, to explore the effects of different plant growth regulator (PGR) combinations on the induction of callus, root formation, and acclimatization in Solanum melongena L. A completely randomized design was employed in a factorial experiment with five replications. The results revealed that, increasing concentrations of gibberellic acid increased germination percentage and seedling length, while germination time decreased. Additionally, results showed superiority in callus induction with the combination of 2 mg l-1 kinetin (Kn.) + 2 mg l-1 Benzyl adenine (BA) + 2 mg l-1 Indole acetic acid (IAA). Root formation varied from 41% to 83% and 1mg l-1 Indole butyric acid (IBA) recorded best significant values. The regenerated plantlets were hardened and acclimatized, and achieving a rate of 90% survivability.